2017
DOI: 10.1111/jgs.15132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Hospital Elder Life Program on Risk of 30‐Day Readmission

Abstract: Objectives To compare rates of 30‐day readmission between hospital units with a Hospital Elder Life Program (HELP) and control units without HELP. Design Retrospective cohort study. Setting The study took place from July 1, 2013, to June 30, 2014, at the University of Pittsburgh Medical Center Shadyside, a 520‐bed community teaching hospital that has used HELP since 2002. Eight medical and surgical units with HELP were compared with 10 medical and surgical units without HELP. Participants During the study peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…A total of 14 studies were included in the meta-analysis 10,1729 and an additional 30 were included as cost-savings studies, methodological papers, and qualitative studies. 9,11–15,27,2951 A flow chart of identification, screening, review, and selection of studies is presented in Figure 1. The meta-analyses presented in Figures 2 and 3 categorized studies as RMTs and non-RMTs.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 14 studies were included in the meta-analysis 10,1729 and an additional 30 were included as cost-savings studies, methodological papers, and qualitative studies. 9,11–15,27,2951 A flow chart of identification, screening, review, and selection of studies is presented in Figure 1. The meta-analyses presented in Figures 2 and 3 categorized studies as RMTs and non-RMTs.…”
Section: Resultsmentioning
confidence: 99%
“…Patients were especially affected by diabetes mellitus and hypertensive heart disease (11.6%), two medical conditions included among the most common noncommunicable diseases by the World Health Organisation (Habib & Saha, 2010). Nonetheless, a minor to moderate severity of illness was found in almost all patients according to the APR‐DRGs, thus suggesting that the complexity of medical condition for the study population was lower than for those generally found in hospitalised patients (Pilotto et al., 2004; Rubin et al., 2018).…”
Section: Discussionmentioning
confidence: 78%
“…Organisation (Habib & Saha, 2010). Nonetheless, a minor to moderate severity of illness was found in almost all patients according to the APR-DRGs, thus suggesting that the complexity of medical condition for the study population was lower than for those generally found in hospitalised patients (Pilotto et al, 2004;Rubin et al, 2018).…”
Section: Characteristics Of the Study Populationmentioning
confidence: 88%
“…Fifth, our attempts to enroll a broad‐based high‐risk patient population may have limited our ability to provide specialized expertise on specific high‐risk conditions. Programs that focus on one condition, such as chronic pulmonary disease and delirium, have been shown to be effective in reducing readmissions . Thus, for some conditions, condition‐specific programs may be more effective than a program targeted to a broader group of hospitalized high‐risk geriatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Programs that focus on one condition, such as chronic pulmonary disease and delirium, have been shown to be effective in reducing readmissions. 43,44 Thus, for some conditions, condition-specific programs may be more effective than a program targeted to a broader group of hospitalized high-risk geriatric patients. Disease-specific programs may not, however, be optimal in the SNF setting because of the multiple and nonspecific nature of acute changes in condition that result in hospital transfers.…”
Section: Discussionmentioning
confidence: 99%